Drivers of Predator Killing by Rural Residents and Recommendations for Fostering Coexistence in Agricultural Landscapes - Gálvez, Nicolás; St. John, Freya A. V.; Davies, Zoe G. (Frontiers in Conservation Science, 2021)
Predators inhabiting human-dominated landscapes are vulnerable to various anthropogenic actions, including people killing them. We assess potential drivers of predator killing in an agricultural landscape in southern Chile, and discuss the implications for policies and interventions to promote coexistence. We evaluate five different types of motivation: (i) sociodemographics and household economy; (ii) livestock loss; (iii) predator encounter rates; (iv) knowledge of legal protection (all native predators are currently protected); and, (v) tolerance to livestock predation. As the killing of native predators is illegal, the prevalence of this behaviour by rural residents was estimated using a symmetrical forced-response randomised response technique (RRT), a method designed to ask sensitive questions. A total of 233 rural residents from randomly assigned sample units (4 km2) across the study region completed our questionnaire. More conspicuous species, such as hawks (Falconiformes sp), foxes (Lycalopex sp) and free-roaming domestic dogs (Canis lupus familiaris), were killed by a higher proportion of farmers than more cryptic species, like the felid güiña (Leopardus guigna), skunk (Conepatus chinga) and pumas (Puma concolor). The proportion of respondents admitting to killing predators was highest for hawks (mean= 0.46, SE= 0.08), foxes (mean= 0.29, SE= 0.08) and dogs (mean= 0.30, SE= 0.08) and lowest for güiña (mean= 0.10, SE = 0.09), which is the only species of conservation concern we examine (considered Vulnerable on the IUCN Red List). From our five motivation categories, past killing of predators was associated with higher reported predator encounter rates (guina, hawks), lower tolerance to livestock predation (hawks, dogs), higher reported livestock loss (dogs) and sociodemographics and household economy (foxes). Our results demonstrate that a one-size-fits-all approach to predator persecution is unlikely to reduce or eliminate illegal killings for the suite of species we examined. We identify and describe two main types of intervention that could foster coexistence, improvement of livestock management and domestic dog management in rural areas, as well as discussing the potential for social marketing.